Broadening the social investment agenda: The OECD, the World Bank and inclusive growth. (April 2019) - Mahon, Rianne
Towards the close of the 20th century, the idea of social investment gained purchase as a way to legitimise social policy as a productive contribution. For those in the North, social investment provided a new rationale to counter neoliberal attacks on the welfare state, while in the South, the idea caught on in the form of conditional cash transfers. The World Bank and Organisation for Economic Development and Cooperation (OECD) played key roles in the development and diffusion of the social investment agenda beginning in the mid-1990s. While hewing to a common core, their interpretations of social investment differed in important respects. The OECD sought to grapple with the emergence of more flexible, post-industrial labour markets, marked by growing precarity, dualisation and feminisation and focused on work–family balance as a solution while the Bank, focused on the South, emphasised social investment in very poor children to break the intergenerational cycle of poverty. In response to new pro-equality movements and intellectual research documenting the growth in inequality, however, a decade later, both organisations moved to incorporate a broader orientation, focused on the concept of 'inclusive growth'. This article explores these developments.